Prevalence of Diabetic Retinopathy and Associated Risk Factors in Diabetic Type II Patients in Ajdabiya, Libya - Bin Hasan, Hanan; Anwar Gibril (AlQalam Journal of Medical and Applied Sciences, 2024)
Diabetic retinopathy (DR) is One of the most well-known microvascular complications of diabetes mellitus (DM) and is a frequent side effect of untreated diabetes that can lead to blindness and visual impairment. This study was conducted to assess the prevalence of diabetic retinopathy and associated factors among type 2 diabetic patients. A cross sectional study was done at Ajdabiya diabetic center from November 2023 to January 2024. Subjects and Methods: 52 patients (104 eyes) with T2DM were included in this study, their fasting blood sugar and glycosylated hemoglobin level, lipid profile measured.in addition to fundus examination (done by noncontact +90-diopter lens), fundus photographs taken by Non-Mydriatic Fundus Camera TFC-1000. Around 61 eyes (58.7%) had diabetic retinopathy, 27 eyes (26%) had back ground DR, 6 eyes (5.8 %) had pre-proliferative DR, 4 eyes (3.8%) had proliferative DR, 2 eyes (1.9%) had advanced diabetic eye disease, 22 eyes (21.2%) had CSME. Their ages ranges between 36–74 years with mean (58.90) years, (26.9%) were males, (73.1%) were females. There was a significant association between the development of DR and duration of DM (p=0.003), The FBS levels were also determined to be a significant risk factor for DR (p = 0.031), also LDL with (p=0.039). No other factors were found to have a significant association with DR. In this study more than half of diabetic patients had diabetic retinopathy. There was a significant association between the development of DR and duration of DM, FBS, LDL levels, there was no significant relation between diabetic retinopathy and hypertension, HgA1c Serum cholesterol or triglyceride levels or previous cataract surgery. اعتلال الشبكية السكري هو أحد أكثر مضاعفات الأوعية الدموية الدقيقة المعروفة لمرض السكري وهو أحد الآثار الجانبية المتكررة لمرض السكري غير المعالج الذي يمكن أن يؤدي إلى العمى وضعف البصر. أجريت هذه الدراسة لتقييم مدى انتشار اعتلال الشبكية السكري والعوامل المرتبطة به بين مرضى السكري من النوع الثاني. التصميم: تم إجراء دراسة مقطعية في مركز أجدابيا للسكري في الفترة من نوفمبر 2023 إلى يناير 2024. تم تضمين 52 مريضًا (104 عيون) يعانون من مرض السكري من النوع الثاني في هذه الدراسة، وتم قياس نسبة السكر في الدم أثناء الصيام ومستوى الهيموجلوبين الغليكوزيلاتي وقياس مستوى الدهون. بالإضافة إلى فحص قاع العين (الذي تم إجراؤه بواسطة عدسة +90 ديوبتر غير لاصقة)، تم التقاط صور قاع العين بواسطة كاميرا قاع العين غير الموسع للحدقة TFC-1000. حوالي 61 عينًا (58.7%) مصابة باعتلال الشبكية السكري، و27 عينًا (26%) مصابة باعتلال الشبكية السكري DR الأرضي، 6 عيون (5.8%) بها DR ما قبل التكاثري، 4 عيون (3.8%) بها DR تكاثري، عينان (1.9%) مصابتان بمرض العين السكري المتقدم، 22 عينًا (21.2%) مصابان بوذمة بقعية هامة سرسريا. تتراوح أعمارهم بين 36 - 74 سنة، بمتوسط (58.90) سنة، (26.9%) ذكور، (73.1%) إناث.هناك ارتباط كبير بين تطور اعتلال الشبكية السكري ومدة الاصابة بمرض السكري(p = 0.003). تم تحديد مستويات السكر في الدم أثناء الصيام أيضًا لتكون عامل خطر مهم لأعتلال الشبكية السكري (p = 0.031) ، وكذلك مع مستوى البروتين الدهني منخفض الكثافة (p = 0.039). لم يتم العثور على عوامل أخرى لها ارتباط كبير مع اعتلال الشبكية السكري. في هذه الدراسة، كان أكثر من نصف مرضى السكري يعانون من اعتلال الشبكية السكري، واعتلال الشبكية السكري الخلفي هو العرض الأكثر انتشارا. كان هناك ارتباط كبير بين تطور اعتلال الشبكية السكريومدة الاصابة بمرض السكري ومستويات السكر في الدم أثناء الصيام و البروتين الدهني منخفض الكثافة؛ لم تكن هناك علاقة ذات دلالة إحصائية بين اعتلال الشبكية السكري وارتفاع ضغط الدم، أو مستويات الكوليسترول في الدم ومستوى الهيموجلوبين الغليكوزيلاتي أو الدهون الثلاثية، أو جراحة الساد السابقة